Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

A novel heteropeptide self-assembly-cascaded dual-enzyme (HSC-DE) system for cascade synthesis of enzymatically modified isoquercitrin (EMIQ) from rutin and sucrose - Ruo-Xi Mei; Tian Xia; Ji-Ming Guo; Ding Wang; Zhi-Ang Zhang; Yan Xu; Richard Ansah Herman; Jun Wang (Food Chemistry, 2026)

Chemical analysis of mulberry (Morus alba L.) leaves treated with jasmonates on nutrition composition and biological activity - Zhi-Ang Zhang; Jia-Ying Liu; Jia-Le Tian; Marriam Khurshid; Cheng-Hai Yan; Richard Ansah Herman; Lu-Chan Gong; Jun Wang (Food Chemistry, 2025)

60Co-γ-ray-irradiated edible silkworm (Bombyx mori) pupae-assisted protease digestion: A strategy for obtaining low molecular weight bioactive peptides - Xiao-Meng Xun; Cheng-Hai Yan; Zi-Xuan Yuan; Zhi-Ang Zhang; Richard Ansah Herman; Yan Xu; Qiong-Ying Wu; Jun Wang (Sustainable Chemistry and Pharmacy, 2025)

Mulberry (Morus alba L.) leaf powder modified the processing of meat alternatives: Principal component analysis from apparent properties to chemical bonds - Zhi-Ang Zhang; Xiao-Meng Xun; Richard Ansah Herman; Zhan-Peng Zhang; Cheng-Hai Yan; Lu-Chan Gong; Jun Wang (Food Chemistry, 2024)

Food Insecurity in the US: An International Student Perspective - Kelly Ang; Soonwye Lucero; Kanae Lee; Andrea Barney; Carol Mathusek; Victoria Thomas; Jinan Banna; Jenny Jackson; Stephanie Grutzmacher; Kendra OoNorasak; Nathan Stokes; Rickelle Richards (Journal of Nutrition Education and Behavior, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Vascular KATP channels protect from cardiac dysfunction and preserve cardiac metabolism during endotoxemia - Qadeer Aziz; Jianmin Chen; Amie J Moyes; Yiwen Li; Naomi A Anderson; Richard Ang; Dunja Aksentijevic; Sonia Sebastian; Adrian J Hobbs; Christoph Thiemermann; Andrew Tinker (Journal of Molecular Medicine, 2020)
K ATP channels in the vasculature composed of Kir6.1 regulate vascular tone and may contribute to the pathogenesis of endotoxemia. We used mice with cell-specific deletion of Kir6.1 in smooth muscle (smKO) and endothelium (eKO) to investigate this question. We found that smKO mice had a significant survival disadvantage compared with their littermate controls when treated with a sub-lethal dose of lipopolysaccharide (LPS). All cohorts of mice became hypotensive following bacterial LPS administration; however, mean arterial pressure in WT mice recovered to normal levels, whereas smKO struggled to overcome LPS-induced hypotension. In vivo and ex vivo investigations revealed pronounced cardiac dysfunction in LPS-treated smKO, but not in eKO mice. Similar results were observed in a cecal slurry injection model. Metabolomic profiling of hearts revealed significantly reduced levels of metabolites involved in redox/energetics, TCA cycle, lipid/fatty acid and amino acid metabolism. Vascular smooth muscle-localised K ATP channels have a critical role in the response to systemic infection by normalising cardiac function and haemodynamics through metabolic homeostasis. Key messages • Mice lacking vascular K ATP channels are more susceptible to death from infection. • Absence of smooth muscle K ATP channels depresses cardiac function during infection. • Cardiac dysfunction is accompanied by profound changes in cellular metabolites. • Findings from this study suggest a protective role for vascular K ATP channels in response to systemic infection.

A comparison of the antifouling performance of air plasma spray (APS) ceramic and high velocity oxygen fuel (HVOF) coatings for use in marine hydraulic applications - Richard Piola; Andrew S. M. Ang; Matthew Leigh; Scott A. Wade (Biofouling, 2018)

Herbarium records do not predict rediscovery of presumed nationally extinct species - Kwek Yan Chong; Serena M. L. Lee; Aik Teck Gwee; Paul K. F. Leong; Samsuri Ahmad; Wee Foong Ang; Alvin F. S. L. Lok; Chow Khoon Yeo; Richard T. Corlett; Hugh T. W. Tan (Biodiversity and Conservation, 2012)

Positive end expiratory pressure as a method for preventing acute mountain sickness - Gustave Savourey; Richard Caterini; Jean-Claude Launay; Anglique Guinet; Yves Besnard; Anne-Marie Hanniquet; Jacques Bittel (European Journal of Applied Physiology, 1997)